A high performance single-layer ceramic capacitor material and preparation method

Through the coordinated design of surface-modified zirconia whiskers and strontium titanate nanoribbons, the problem of insufficient dielectric properties and mechanical strength and toughness of the single-layer porcelain dielectric capacitor materials is solved, and the high dielectric properties and long-term stability of the material are achieved, which is suitable for high-end electronic components.

CN119735437BActive Publication Date: 2025-05-09ZHUZHOU HONGDA HENGXIN ELECTRONIC CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510254689.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-03-05
Publication Date
2025-05-09
Estimated Expiration
2045-03-05

AI Technical Summary

Technical Problem

The existing single-layer porcelain dielectric capacitor materials have shortcomings in dielectric properties and mechanical strength and toughness, and it is difficult to meet the needs of high-frequency and high-power electronic devices for low loss and high reliability.

Method used

The coordinated design of surface-modified zirconia whiskers and strontium titanate nanoribbons is adopted, and the silane coupling agent is introduced through ultrasonic treatment of sulfuric acid solution and hydrothermal reaction. The modified zirconia whiskers are combined with the coherent interface of barium titanate/strontium titanate to optimize the microstructure and interface binding force of the material.

Benefits of technology

It significantly improves the fracture toughness and mechanical impact resistance of the material, while maintaining stable dielectric constant and low loss characteristics, meeting the demands of high-end electronic components for high dielectric performance and long-term stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119735437B_ABST
    Figure CN119735437B_ABST
Patent Text Reader

Abstract

The present invention relates to the field of capacitor materials, and provides a high-performance single-layer ceramic capacitor material and a preparation method thereof. The material comprises surface-modified zirconium oxide whiskers, strontium titanate nanobelts, barium titanate nanoparticles, barium nitrate, tetraisopropyl titanate, tetramethylammonium hydroxide, ammonium polyacrylate, lanthanum oxide, niobium oxide, manganese dioxide, nano-silicon dioxide and an ethanol-water mixed solution. The zirconium oxide whiskers are modified with a KH-550 silane coupling agent to improve the dispersibility and interfacial bonding force of the reinforcing phase. The introduction of strontium titanate nanobelts optimizes the coherent interface of barium titanate / strontium titanate, and improves the dielectric properties and mechanical strength of the material. Ultrasonic dispersion, ball milling mixing, doping tape casting and gradient sintering processes are adopted to enable the material to achieve high density, low dielectric loss and excellent temperature stability. The present invention overcomes the deficiencies of existing single-layer ceramic capacitor materials in dielectric properties and mechanical strength, and is suitable for the field of high-reliability electronic component manufacturing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of capacitor materials, and in particular to a high-performance single-layer ceramic capacitor material and a preparation method thereof. Background Art

[0002] In high-frequency, high-power electronic devices, aerospace, 5G communications and advanced computing systems, single-layer ceramic capacitors are one of the key passive components and are widely used in core circuits such as signal conditioning, energy storage and electromagnetic interference suppression. As electronic equipment develops towards high integration, miniaturization and high reliability, higher performance requirements are placed on capacitor materials, especially dielectric properties and mechanical strength and toughness. Excellent dielectric properties, including high dielectric constant, low dielectric loss and good temperature stability, can effectively improve the energy storage capacity and working stability of capacitors, and meet the needs of high-frequency, high-power circuits for low loss and high reliability. At the same time, single-layer ceramic capacitors need to withstand complex environments such as sintering stress, mechanical shock and thermal cycling during manufacturing and application. Therefore, the strength and toughness of the material are crucial to ensure the structural integrity and mechanical durability of the device under long-term working conditions. Especially in harsh environments, such as aerospace and automotive electronic systems, the crack resistance and fatigue resistance of the material directly affect the product life and reliability. Therefore, the development of single-layer ceramic capacitor materials with both high dielectric properties and excellent mechanical properties can not only improve the overall performance of the device, but also promote technological innovation of electronic components and expand their application scope in high-end electronic equipment.

[0003] Existing single-layer ceramic capacitor materials still have many deficiencies in dielectric properties and mechanical strength and toughness. For example, the Chinese patent with publication number CN106633142A discloses a graphene barium titanate polyimide composite film material for high specific capacitance film capacitors and its preparation method. Although the dielectric constant is improved to a certain extent, its dielectric loss is high and its stability is poor under high temperature and high frequency environments, which limits its use in high reliability applications. At the same time, due to the strong intrinsic brittleness of traditional barium titanate-based ceramics, the material is prone to microcracks under mechanical shock or thermal cycling, resulting in reduced capacitor reliability. In addition, some existing technologies optimize sintering characteristics by introducing glass phases or low melting point additives, but often reduce the mechanical properties of the material, making the device more prone to mechanical failure in practical applications. On the other hand, some studies have attempted to improve the toughness of materials through nanoengineering means or composite structure design, but due to interface effects, compatibility issues or complexity of the preparation process, practical applications are limited. Therefore, there is an urgent need to develop a new single-layer ceramic capacitor material with both high dielectric properties and excellent mechanical properties to overcome the limitations of existing materials and meet the requirements of modern electronic devices for high reliability and long life. Summary of the invention

[0004] (1) Technical problems solved

[0005] The purpose of the present invention is to provide a high-performance single-layer ceramic capacitor material and a preparation method to solve the problem that the current single-layer ceramic capacitor material has insufficient dielectric properties and toughness properties.

[0006] (2) Technical solution

[0007] In order to achieve the above object, the present invention provides the following technical solutions:

[0008] A high-performance single-layer ceramic capacitor material comprises the following raw materials in parts by weight: 8.0-12.0 parts of surface-modified zirconium oxide whiskers, 10.0-18.0 parts of strontium titanate nanobelts, 60.0-75.0 parts of barium titanate nanoparticles, 5.0-8.0 parts of barium nitrate, 4.0-6.0 parts of tetraisopropyl titanate, 2.0-4.0 parts of tetramethylammonium hydroxide, 0.3-0.8 parts of ammonium polyacrylate, 1.0-2.0 parts of lanthanum oxide, 0.5-1.2 parts of niobium oxide, 0.1-0.5 parts of manganese dioxide, 0.3-0.8 parts of nano silicon dioxide, and 100.0 parts of a mixed solution of ethanol and water.

[0009] The surface modified zirconium oxide whisker is obtained by surface modification of zirconium oxide whisker with silane coupling agent KH-550;

[0010] The single-layer ceramic capacitor material comprises a barium titanate / strontium titanate coherent interface.

[0011] Furthermore, the preparation method of the surface modified zirconium oxide whisker is characterized in that: by weight, 8.0-12.0 parts of zirconium oxide whisker are immersed in 30.0-50.0 parts of 3.0-5.0 mol / L sulfuric acid solution, and ultrasonically treated at 60-80° C. for 30-60 min; then the mixture is transferred to a high-pressure reactor, 0.4-1.2 parts of silane coupling agent KH-550 are added, and hydrothermally reacted at 120-150° C. for 60-12 0min; after the reaction is completed, centrifuge at 8000~12000rpm, and wash the solid part with 50.0~80.0 parts of deionized water until neutral; then disperse the modified whiskers in 100.0 parts of an aqueous solution containing 0.08~0.6 parts of ammonium polyacrylate, and ultrasonically treat for 20~40min; filter and collect the solid powder, and finally dry it at 80~100℃ and 10⁻²~10⁻³Pa for 6~12 hours to obtain surface modified zirconia whiskers.

[0012] Furthermore, the surface modified zirconia whiskers have an average diameter of 0.5-2.0 μm and an average length of 5-20 μm.

[0013] Furthermore, the preparation method of the zirconia whisker is as follows: 1.8 to 2.2 parts of zirconium oxychloride octahydrate and 1.8 to 2.2 parts of mixed salt are weighed in parts by weight and placed in a mortar, wherein the mixed salt is sodium chloride and lithium chloride compounded in a mass ratio of 1: (1 to 1.5), the obtained solid mixture is fully ground for 10 to 30 minutes until it is uniform, and then the obtained precursor mixture is transferred to a corundum crucible with a lid, and placed in a high-temperature furnace, and heated to 900 to 1000° C. at a heating rate of 3 to 7° C. / min at room temperature, and after keeping warm for 240 to 360 minutes, the furnace power is then turned off, and the reaction system is allowed to cool naturally to room temperature with the furnace, and the cooled solid product is washed with deionized water 3 to 5 times to remove residual molten salt, and dried at 60 to 80° C. for 5 to 7 hours to finally obtain zirconia whiskers.

[0014] The present invention adopts the design of surface modified zirconium oxide whisker mainly for enhancing the mechanical strength and dielectric properties of single-layer ceramic capacitor materials. The surface hydroxyl groups of zirconium oxide whisker are activated by ultrasonic treatment of sulfuric acid solution, and silane coupling agent KH-550 is introduced under hydrothermal conditions to form a stable chemical bond with the whisker surface, thereby improving the dispersibility and interface bonding force of zirconium oxide whisker in the matrix. The modified zirconium oxide whisker is further dispersed by the auxiliary of ammonium polyacrylate in the subsequent solution system to further reduce the agglomeration phenomenon, so that it can be evenly distributed in the dielectric matrix composed of barium titanate and strontium titanate. This evenly distributed reinforcement phase not only optimizes the microstructure of the ceramic material, but also effectively alleviates the stress concentration in the sintering process, and improves the fracture toughness and mechanical impact resistance of the material. In addition, the introduction of zirconium oxide whisker helps to improve the dielectric loss characteristics of the ceramic material, so that the material can still maintain a stable dielectric constant and low loss characteristics under a high-frequency electric field. By optimizing the size parameters of zirconia whiskers and controlling their diameter and length range, they can provide effective reinforcement in the ceramic matrix while avoiding excessive impact on dielectric properties, thereby achieving a balance between mechanical properties and electrical properties. During the preparation of zirconia whiskers, a high-temperature solid-phase method combined with molten salt-assisted growth technology is used to ensure the high purity and high crystallinity of the whiskers, providing a stable physical basis for their subsequent surface modification and dispersion. Ultimately, the present invention achieves excellent mechanical strength and long-term reliability for single-layer ceramic capacitor materials while maintaining high dielectric properties through fine control of zirconia whiskers, making it suitable for the field of high-end electronic component manufacturing.

[0015] Further, the preparation method of the strontium titanate nanobelt is as follows: by weight, 17 to 34 parts of tetrabutyl titanate and 80 to 120 parts of ethylene glycol are mixed and ultrasonically treated for 10 to 15 minutes to obtain a suspension, then 12.0 to 24 parts of strontium chloride hexahydrate are added and ultrasonically treated for 15 to 20 minutes, and then 50 to 60 parts of 4 mol / L KOH solution are added, and then stirred at a stirring speed of 200 to 250 rpm for 10 to 16 minutes. After the stirring is completed, the mixed solution is transferred to a stainless steel autoclave lined with polytetrafluoroethylene, sealed and placed in a constant temperature oven at 160 to 200° C. for a hydrothermal reaction for 1 8~24h, after the reaction is completed, turn off the heating source and allow the reactor to cool naturally to room temperature. The cooled reaction product is separated by centrifugation at a centrifugal rate of 8000~10000rpm for 10~15 to separate the precipitate, the filtrate is discarded, and the obtained precipitate is washed alternately with deionized water and anhydrous ethanol for 3~5 times in turn. The washed precipitate is transferred to a vacuum drying oven and dried at 50~80℃ for 10~15h to obtain an off-white powder. The dried powder is transferred to a muffle furnace and heated to 600~800℃ at a heating rate of 3~6℃ / min. After keeping warm for 60~120min, it is cooled to room temperature to obtain strontium titanate nanobelts.

[0016] Furthermore, the average width of the strontium titanate nanobelt is 30-100 nm, and the average length is 1-5 μm.

[0017] The present invention adopts the design of strontium titanate nanobelts mainly for enhancing the dielectric properties and structural stability of single-layer ceramic capacitor materials. The uniformity of the precursor solution is ensured by ultrasonic dispersion of tetrabutyl titanate and ethylene glycol, and the uniform distribution of the strontium source is further promoted by ultrasound under the introduction of strontium chloride hexahydrate, thereby optimizing the subsequent crystal growth process. Under alkaline conditions, the addition of KOH solution regulates the pH value of the reaction system, so that the strontium titanate precursor can be stably formed, and the uniformity of the components is further improved under stirring. In the hydrothermal reaction stage, the constant temperature condition promotes the directional growth of the nanobelts, so that it obtains higher crystal integrity and structural regularity, while avoiding the formation of granular precipitation, ensuring that the final product has a higher aspect ratio. In the subsequent separation and washing process, deionized water and anhydrous ethanol are used for alternating washing to effectively remove by-products and residual alkaline substances, thereby ensuring the purity of the final product. The vacuum drying process reduces the possibility of agglomeration of the nanobelts, and the subsequent muffle furnace heat treatment further optimizes its crystallinity, so that it has excellent physical stability and chemical purity. The size parameters of strontium titanate nanobelts are strictly controlled so that they can be evenly distributed in the subsequent ceramic matrix and form a stable barium titanate / strontium titanate coherent interface in the barium titanate matrix, thereby optimizing the dielectric properties of the material, reducing dielectric loss, improving temperature stability, and ensuring the reliability of the material under long-term service conditions. The present invention maximizes the enhancement effect of strontium titanate nanobelts in single-layer ceramic capacitor materials by precisely controlling the preparation process of strontium titanate nanobelts, achieving a balance between high dielectric properties and long-term stability, and meeting the application requirements of high-end electronic components.

[0018] The present invention adopts the synergistic design of surface-modified zirconium oxide whiskers and strontium titanate nanobelts, which is mainly used to enhance the dielectric properties, mechanical strength and long-term stability of single-layer ceramic capacitor materials. After the zirconium oxide whiskers are modified by the silane coupling agent KH-550, their surface activity is optimized, and they can be evenly dispersed in the solution system, and through the synergistic effect with barium titanate nanoparticles and strontium titanate nanobelts, the structural uniformity and interfacial bonding force of the material are improved. The introduction of strontium titanate nanobelts forms a coherent interface at the grain boundary of the barium titanate main material, thereby improving the dielectric properties, reducing dielectric loss, and improving the temperature stability of the material. Barium nitrate and tetraisopropyl titanate are used as precursors to provide the necessary chemical components for the formation of the barium titanate matrix, while the addition of tetramethylammonium hydroxide helps to regulate the pH value of the solution, ensure the stability of the precursor, and promote the uniform dispersion of subsequent nanofillers. Ammonium polyacrylate further improves the rheological properties of the slurry, so that the material remains evenly distributed during the tape casting process, avoiding local agglomeration and affecting the density of the final sintered body. The doping of lanthanum oxide, niobium oxide and manganese dioxide optimizes the dielectric properties and sintering characteristics of the material, enhances the densification process, and reduces the leakage current loss of the material. The introduction of nano-silicon dioxide promotes grain boundary strengthening during high-temperature sintering, improves the mechanical strength of the material, and improves the long-term reliability of the sintered body. The mixed solution of ethanol and water serves as a solvent system to provide a uniform dispersion medium for the sol-gel process, ensuring uniform mixing of the components in the entire system. The synergistic effect between the components enables the single-layer ceramic capacitor material of the present invention to have excellent mechanical strength and long-term stability while maintaining high dielectric properties, meeting the application requirements of high-end electronic components.

[0019] Furthermore, the volume ratio of ethanol to water in the ethanol and water mixed solution is 1: (2.0-4.0).

[0020] The present invention also discloses a method for preparing a high-performance single-layer ceramic capacitor material, comprising the following steps:

[0021] S1. Precursor solution: According to the weight ratio, barium nitrate and tetraisopropyl titanate are dissolved in a mixed solution of ethanol and water, and then tetramethylammonium hydroxide is slowly added. The mixture is ultrasonically treated at 250-300 W and 30-40 kHz for 30-45 min in a 40°C water bath to obtain a precursor solution.

[0022] S2. Pre-dispersion of the reinforcing phase: Add surface-modified zirconia whiskers and strontium titanate nanobelts to the above precursor solution, and add ammonium polyacrylate. Then, place the mixed slurry in a planetary ball mill, use zirconia ball media, and ball mill at a speed of 200-300 rpm for 60-120 minutes. The viscosity of the slurry after ball milling is 250-400 mPa·s.

[0023] S3. Doping and tape casting: Lanthanum oxide, niobium oxide and manganese dioxide, barium titanate nanoparticles and nano-silicon dioxide are added to the above slurry in sequence, and ultrasonic-mechanical stirring is used for coordinated treatment. The ultrasonic power is 400-500 W, the stirring rate is 450-600 rpm, and the treatment time is 30-45 min. Subsequently, a tape casting machine is used to form a wet film on the polyimide base film, and it is cured at 30-40 ° C and 30% RH for 300-420 min to obtain a dry film.

[0024] S4. Gradient sintering treatment: Place the cured dry membrane in an atmosphere sintering furnace, and at an oxygen flow rate of 50~100mL / min, heat it to 550~600℃ at a rate of 3~5℃ / min for organic matter removal treatment. The treatment time is 30~45min. Then, continue to heat it to 1100~1200℃ at a rate of 3~5℃ / min for sintering. After sintering, anneal it in an oxygen atmosphere at 850~900℃ for 60~120min, and finally cool it in the furnace.

[0025] The present invention adopts optimized precursor preparation, reinforcing phase dispersion, doping tape casting and gradient sintering designs, which are mainly used to enhance the dielectric properties, mechanical strength and structural stability of single-layer ceramic capacitor materials. In the preparation process of the precursor solution, the dissolution of barium nitrate and tetraisopropyl titanate provides a uniform barium-titanium source, and the mixed solution of ethanol and water as a solvent system ensures uniform dispersion. The pH value of the solution is regulated by the slow addition of tetramethylammonium hydroxide, and the uniform dispersion of the precursor is promoted in combination with ultrasonic treatment, thereby improving the stability of the subsequent material. In the pre-dispersion process of the reinforcing phase, the co-introduction of surface-modified zirconium oxide whiskers and strontium titanate nanobelts optimizes the mechanical properties and dielectric stability of the material, wherein the high-strength characteristics of the zirconium oxide whiskers enhance the toughness of the ceramic matrix, and the addition of strontium titanate nanobelts improves the coherent interface of the barium titanate body and reduces the dielectric loss. The addition of ammonium polyacrylate further enhances the dispersibility of the nanofiller, and under the action of a planetary ball mill, the slurry achieves suitable rheological properties, providing good processing characteristics for subsequent tape casting. During the doping and tape-casting stages, the addition of lanthanum oxide, niobium oxide and manganese dioxide optimizes the dielectric properties of the material, and the ultrasonic-mechanical stirring synergistic treatment ensures the uniform distribution of the doping elements. The introduction of nano-silicon dioxide further improves the sintering density, which helps to improve the long-term reliability of the material. Finally, during the gradient sintering process, the appropriate heating rate and oxygen flow rate control ensure the full removal of organic matter, and promote the densification of the ceramic matrix during the high-temperature sintering stage. The annealing treatment further reduces the defect concentration of the material and optimizes the dielectric properties and temperature stability. The synergistic effect between the various process steps enables the single-layer ceramic capacitor material of the present invention to have both high mechanical strength and long-term stability while maintaining excellent dielectric properties, meeting the application requirements of high-end electronic components.

[0026] (3) Beneficial technical effects

[0027] 1. The present invention achieves the synergistic optimization of the dielectric properties and mechanical strength of the single-layer ceramic capacitor material by introducing surface-modified zirconia whiskers. Compared with the prior art, the fracture toughness and mechanical impact resistance of the material are significantly improved, while maintaining a stable dielectric constant and low loss characteristics. Ultrasonic treatment with sulfuric acid solution enhances the hydroxyl activity on the whisker surface, and the hydrothermal modification of the KH-550 coupling agent improves its dispersibility and interfacial bonding in the dielectric matrix. With the auxiliary effect of ammonium polyacrylate, it effectively prevents agglomeration and optimizes the microstructure. The optimized whisker size parameters ensure the balance between the enhancement effect and the dielectric stability. The combination of high-temperature solid-phase method and molten salt-assisted growth technology ensures the high purity and high crystallinity of the material, thereby showing excellent reliability and application value in the manufacture of high-end electronic components.

[0028] 2. The present invention achieves the coordinated optimization of the dielectric properties and structural stability of single-layer ceramic capacitor materials through the precise design of strontium titanate nanobelts. Compared with the prior art, the dielectric constant is significantly improved, the dielectric loss is reduced, and the temperature stability and long-term reliability of the material are enhanced. Ultrasonic dispersion ensures the uniformity of the precursor solution, KOH regulates the pH to stabilize the precursor, and the hydrothermal reaction promotes the directional growth of the nanobelts, so that a stable barium titanate / strontium titanate coherent interface is formed in the barium titanate matrix, thereby optimizing the dielectric properties. Alternating washing with deionized water and anhydrous ethanol improves purity, vacuum drying and heat treatment optimize crystallinity, ensure uniform distribution of the nanobelts, and ultimately meet the needs of high-end electronic components for high dielectric properties and long-term stability.

[0029] 3. The present invention optimizes the high dielectric properties, mechanical strength and long-term stability of single-layer ceramic capacitor materials through the synergistic effect of surface-modified zirconium oxide whiskers and strontium titanate nanobelts. Compared with the prior art, it significantly reduces dielectric loss, improves temperature stability, and enhances the structural uniformity and interfacial bonding of the material. The modification of zirconium oxide whiskers improves its dispersibility, and together with barium titanate nanoparticles and strontium titanate nanobelts, it optimizes the microstructure and ensures the stability of grain boundaries. Tetramethylammonium hydroxide regulates pH, ammonium polyacrylate improves rheological properties, doping elements optimize sintering characteristics, and nano-silicon dioxide strengthens grain boundaries, ultimately making the material show excellent reliability and application value in high-end electronic components.

[0030] 4. The present invention achieves the synergistic optimization of the dielectric properties, mechanical strength and structural stability of the single-layer ceramic capacitor material by optimizing the precursor preparation, enhancing phase dispersion, doping tape casting and gradient sintering. Compared with the prior art, the dielectric loss is significantly reduced, and the density and long-term reliability are improved. Modified zirconium oxide whiskers enhance toughness, strontium titanate nanobelts optimize the coherent interface, ammonium polyacrylate improves rheological properties, uniform distribution of doping elements improves dielectric stability, and nano-silicon dioxide strengthens sintering and densification. Finally, high-performance dielectric materials are obtained under gradient sintering and annealing treatment to meet the stringent requirements of high-end electronic components. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 This is a morphology picture of the surface modified zirconia whisker prepared in Example 1 of the present invention.

[0032] Figure 2 This is a phase diagram of the surface modified zirconia whiskers prepared in Example 1 of the present invention.

[0033] Figure 3 This is a morphology picture of the strontium titanate nanobelt prepared in Example 1 of the present invention.

[0034] Figure 4 This is a phase analysis diagram of the strontium titanate nanobelt prepared in Example 1 of the present invention.

[0035] Figure 5 This is a diagram of the crack propagation path in the microstructure of the single-layer ceramic capacitor material prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0036] To make the purpose, technical solution and advantages of the embodiments of the present invention more clear, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the accompanying drawings in the embodiments of the present invention.

[0037] Embodiment 1: A high-performance single-layer ceramic capacitor material comprises the following raw materials in parts by weight: 8.0 parts of surface modified zirconium oxide whiskers, 10.0 parts of strontium titanate nanobelts, 60.0 parts of barium titanate nanoparticles, 5.0 parts of barium nitrate, 4.0 parts of tetraisopropyl titanate, 2.0 parts of tetramethylammonium hydroxide, 0.3 parts of ammonium polyacrylate, 1.0 parts of lanthanum oxide, 0.5 parts of niobium oxide, 0.1 parts of manganese dioxide, 0.3 parts of nano-silicon dioxide, and 100.0 parts of a mixed solution of ethanol and water.

[0038] The surface modified zirconium oxide whisker is obtained by surface modification of zirconium oxide whisker by using silane coupling agent KH-550; the single-layer ceramic dielectric capacitor material comprises a barium titanate / strontium titanate coherent interface.

[0039] The preparation method of the surface modified zirconia whisker of the present embodiment is as follows: characterized in that: by weight, 8.0 parts of zirconia whiskers are immersed in 30.0 parts of 3.0 mol / L sulfuric acid solution, and ultrasonically treated at 60°C for 30 minutes; then the mixture is transferred to a high-pressure reactor, 0.4 parts of silane coupling agent KH-550 are added, and hydrothermal reaction is carried out at 120°C for 60 minutes; after the reaction is completed, centrifugation is carried out at 8000rpm, and the solid part is washed with 50.0 parts of deionized water until neutral; then the modified whiskers are dispersed in 100.0 parts of an aqueous solution containing 0.08 parts of ammonium polyacrylate, and ultrasonically treated for 20 minutes; the solid powder is filtered and collected, and finally dried at 80°C and 10⁻²Pa for 6 hours to obtain surface modified zirconia whiskers.

[0040] The surface-modified zirconia whiskers of this embodiment have an average diameter of 0.5 μm and an average length of 5 μm.

[0041] The preparation method of the zirconium oxide whisker of the present embodiment is as follows: 1.8 parts of zirconium oxychloride octahydrate and 1.8 parts of mixed salt are weighed and placed in a mortar, wherein the mixed salt is sodium chloride and lithium chloride compounded in a mass ratio of 1:1, and the obtained solid mixture is fully ground for 10 minutes until it is uniform, and then the obtained precursor mixture is transferred to a corundum crucible with a cover, and placed in a high-temperature furnace, and heated to 900°C at a heating rate of 3°C / min at room temperature. After keeping the temperature for 240 minutes, the furnace power is then turned off, and the reaction system is allowed to cool naturally to room temperature with the furnace. The cooled solid product is washed 3 times with deionized water to remove residual molten salt, and dried at 60°C for 5 hours to finally obtain zirconium oxide whiskers.

[0042] The preparation method of the strontium titanate nanobelt of this embodiment is as follows: by weight, 17 parts of tetrabutyl titanate and 80 parts of ethylene glycol are mixed and ultrasonically treated for 10 minutes to obtain a suspension, then 12.0 parts of strontium chloride hexahydrate are added and ultrasonicated for 15 minutes, and then 50 parts of 4 mol / L KOH solution are added, followed by stirring at a stirring speed of 200 rpm for 10 minutes. After the stirring is completed, the mixed solution is transferred to a stainless steel autoclave lined with polytetrafluoroethylene, sealed and placed in a constant temperature oven at 160°C for hydrothermal reaction for 18 h. After the reaction is completed, the heating source is turned off and the reactor is allowed to cool naturally to room temperature. The cooled reaction product is centrifuged at 8000 rpm for 10 to separate the precipitate, the filtrate is discarded, and the obtained precipitate is washed alternately with deionized water and anhydrous ethanol for 3 times. The washed precipitate is transferred to a vacuum drying oven and dried at 50°C for 10 h to obtain an off-white powder. The dried powder is transferred to a muffle furnace and heated to 600°C at a heating rate of 3°C / min. After keeping warm for 60 min, it is cooled to room temperature to obtain strontium titanate nanobelts.

[0043] The average width of the strontium titanate nanobelts in this embodiment is 30 nm, and the average length is 1 μm.

[0044] The volume ratio of ethanol to water in the ethanol and water mixed solution of this embodiment is 1:2.0.

[0045] A method for preparing a high-performance single-layer ceramic capacitor material in this embodiment includes the following steps:

[0046] S1. Precursor solution: barium nitrate and tetraisopropyl titanate are dissolved in a mixed solution of ethanol and water according to the weight ratio, and then tetramethylammonium hydroxide is slowly added. The mixture is ultrasonically treated at 250 W and 30 kHz for 30 min in a 40°C water bath to obtain a precursor solution.

[0047] S2. Pre-dispersion of the reinforcing phase: Add surface-modified zirconia whiskers and strontium titanate nanobelts to the above precursor solution, and add ammonium polyacrylate. Then, place the mixed slurry in a planetary ball mill, use zirconia ball media, and ball mill at 200 rpm for 60 minutes. The viscosity of the slurry after ball milling is 250 mPa·s.

[0048] S3. Doping and tape casting: Lanthanum oxide, niobium oxide, manganese dioxide, barium titanate nanoparticles and nano-silicon dioxide were added to the above slurry in sequence, and ultrasonic-mechanical stirring was used for coordinated treatment. The ultrasonic power was 400 W, the stirring rate was 450 rpm, and the treatment time was 30 min. Subsequently, a tape casting machine was used to form a wet film on the polyimide base film, and the film was cured at 30°C and 30% RH for 300 min to obtain a dry film.

[0049] S4. Gradient sintering treatment: Place the cured dry membrane in an atmosphere sintering furnace, and at an oxygen flow rate of 50 mL / min, heat it to 550°C at a rate of 3°C / min for organic matter removal treatment. The treatment time is 30 minutes. Subsequently, continue to heat it to 1100°C at a rate of 3°C / min for sintering. After sintering, anneal it in an oxygen atmosphere at 850°C for 60 minutes, and finally cool it in the furnace.

[0050] Combination Figures 1 to 5 The experimental results can prove that Example 1 of the present invention successfully prepared surface-modified zirconium oxide whiskers and strontium titanate nanobelts, and further verified their reinforcing effect in ceramic dielectric capacitor materials. Figure 1 The morphological characteristics of zirconia whiskers are shown, indicating that the obtained whiskers have a high aspect ratio, which is consistent with the expected nano-enhanced structure. Figure 2 XRD phase analysis further confirmed the crystal structure of the obtained zirconia whiskers, proving that its phase conforms to the characteristics of modified zirconia. Figure 3 The morphology of strontium titanate nanoribbons is shown, indicating that they have a regular ribbon structure. Figure 4 The phase analysis further confirmed the crystal structure of strontium titanate. Figure 5 The crack propagation path can be clearly observed in the microstructure of the single-layer ceramic capacitor material, where crack bridging and deflection occur on the surface of the zirconia whiskers, verifying the role of zirconia whiskers in improving the toughness of the material and enhancing the fracture resistance, thereby proving that the present invention can effectively improve the mechanical properties of the ceramic capacitor material.

[0051] Embodiment 2: A high-performance single-layer ceramic capacitor material comprises the following raw materials in parts by weight: 9.2 parts of surface modified zirconium oxide whiskers, 12.4 parts of strontium titanate nanobelts, 64.5 parts of barium titanate nanoparticles, 5.9 parts of barium nitrate, 4.6 parts of tetraisopropyl titanate, 2.6 parts of tetramethylammonium hydroxide, 0.5 parts of ammonium polyacrylate, 1.3 parts of lanthanum oxide, 0.7 parts of niobium oxide, 0.2 parts of manganese dioxide, 0.5 parts of nano-silicon dioxide, and 100.0 parts of a mixed solution of ethanol and water.

[0052] The surface-modified zirconium oxide whisker is obtained by surface-modifying the zirconium oxide whisker with a silane coupling agent KH-550; the single-layer ceramic dielectric capacitor material comprises a barium titanate / strontium titanate coherent interface.

[0053] The preparation method of the surface modified zirconia whisker of the present embodiment is as follows: it is characterized in that: by weight, 9.2 parts of zirconia whiskers are immersed in 36.0 parts of 3.6 mol / L sulfuric acid solution, and ultrasonically treated at 66°C for 39 minutes; then the mixture is transferred to a high-pressure reactor, 0.6 parts of silane coupling agent KH-550 are added, and hydrothermal reaction is carried out at 129°C for 78 minutes; after the reaction is completed, centrifugation is carried out at 9200rpm, and the solid part is washed with 59.0 parts of deionized water until neutral; then the modified whiskers are dispersed in 100.0 parts of an aqueous solution containing 0.23 parts of ammonium polyacrylate, and ultrasonically treated for 26 minutes; the solid powder is filtered and collected, and finally dried at 86°C and 10⁻²Pa for 7.8 hours to obtain surface modified zirconia whiskers.

[0054] The surface-modified zirconia whiskers of this embodiment have an average diameter of 0.9 μm and an average length of 9 μm.

[0055] The preparation method of the zirconium oxide whisker of the present embodiment is as follows: 1.9 parts of zirconium oxychloride octahydrate and 1.9 parts of mixed salt are weighed in parts by weight and placed in a mortar, wherein the mixed salt is sodium chloride and lithium chloride compounded in a mass ratio of 1:1.2, and the obtained solid mixture is fully ground for 16 minutes until it is uniform, and then the obtained precursor mixture is transferred to a corundum crucible with a cover, and placed in a high-temperature furnace, and heated to 930°C at a heating rate of 4.2°C / min at room temperature, and after keeping warm for 276 minutes, the furnace power is then turned off, and the reaction system is allowed to cool naturally to room temperature with the furnace, and the cooled solid product is washed 3.6 times with deionized water to remove residual molten salt, and dried at 66°C for 5.6 hours to finally obtain zirconium oxide whiskers.

[0056] The preparation method of the strontium titanate nanobelt of this embodiment is as follows: by weight, 22 parts of tetrabutyl titanate and 92 parts of ethylene glycol are mixed and ultrasonically treated for 11.5 minutes to obtain a suspension, and then 15.6 parts of strontium chloride hexahydrate are added and ultrasonicated for 16.5 minutes, and then 53 parts of 4 mol / L KOH solution are added, and then stirred at a stirring speed of 215 rpm for 11.8 minutes. After the stirring is completed, the mixed solution is transferred to a stainless steel autoclave lined with polytetrafluoroethylene, sealed, and placed in a constant temperature oven at 172°C for a hydrothermal reaction for 19.8 h. After the reaction was completed, the heating source was turned off and the reactor was allowed to cool naturally to room temperature. The cooled reaction product was centrifuged at 8600 rpm for 11.5 to separate the precipitate, the filtrate was discarded, and the obtained precipitate was washed alternately with deionized water and anhydrous ethanol for 3.6 times. The washed precipitate was transferred to a vacuum drying oven and dried at 59°C for 11.5h to obtain an off-white powder. The dried powder was transferred to a muffle furnace and heated to 660°C at a heating rate of 3.9°C / min. After keeping warm for 78 minutes, it was cooled to room temperature to obtain strontium titanate nanobelts.

[0057] The average width of the strontium titanate nanobelts in this embodiment is 51 nm, and the average length is 2.2 μm.

[0058] The volume ratio of ethanol to water in the ethanol and water mixed solution of this embodiment is 1:2.6.

[0059] A method for preparing a high-performance single-layer ceramic capacitor material in this embodiment includes the following steps:

[0060] S1. Precursor solution: barium nitrate and tetraisopropyl titanate are dissolved in a mixed solution of ethanol and water according to the weight ratio, and then tetramethylammonium hydroxide is slowly added. The mixture is ultrasonically treated at 265 W and 33 kHz for 34.5 min in a 40°C water bath to obtain a precursor solution.

[0061] S2. Pre-dispersion of the reinforcing phase: Add surface-modified zirconia whiskers and strontium titanate nanobelts to the above precursor solution, and add ammonium polyacrylate. Then, place the mixed slurry in a planetary ball mill, use zirconia ball media, and ball mill at 230 rpm for 78 minutes. The viscosity of the slurry after ball milling is 295 mPa·s.

[0062] S3. Doping and tape casting: Lanthanum oxide, niobium oxide, manganese dioxide, barium titanate nanoparticles and nano-silicon dioxide were added to the above slurry in turn, and ultrasonic-mechanical stirring was used for coordinated treatment. The ultrasonic power was 430 W, the stirring rate was 495 rpm, and the treatment time was 34.5 min. Subsequently, a tape casting machine was used to form a wet film on the polyimide base film, and it was cured at 33°C and 30% RH for 336 min to obtain a dry film.

[0063] S4. Gradient sintering treatment: Place the cured dry membrane in an atmosphere sintering furnace, and heat it to 565℃ at a rate of 3.6℃ / min under an oxygen flow rate of 65mL / min for organic matter removal treatment. The treatment time is 34.5min. Then, continue to heat it to 1145℃ at a rate of 3.6℃ / min for sintering. After sintering, anneal it in an oxygen atmosphere at 865℃ for 78min, and finally cool it in the furnace.

[0064] Embodiment 3: A high-performance single-layer ceramic capacitor material comprises the following raw materials in parts by weight: 10.4 parts of surface modified zirconium oxide whiskers, 14.8 parts of strontium titanate nanobelts, 69.0 parts of barium titanate nanoparticles, 6.8 parts of barium nitrate, 5.2 parts of tetraisopropyl titanate, 3.2 parts of tetramethylammonium hydroxide, 0.6 parts of ammonium polyacrylate, 1.6 parts of lanthanum oxide, 0.9 parts of niobium oxide, 0.3 parts of manganese dioxide, 0.6 parts of nano-silicon dioxide, and 100.0 parts of a mixed solution of ethanol and water.

[0065] The surface modified zirconium oxide whisker is obtained by surface modification of zirconium oxide whisker by using silane coupling agent KH-550; the single-layer ceramic dielectric capacitor material comprises a barium titanate / strontium titanate coherent interface.

[0066] The preparation method of the surface modified zirconia whisker of the present embodiment is as follows: it is characterized in that: in parts by weight, 10.4 parts of zirconia whiskers are immersed in 42.0 parts of 4.2 mol / L sulfuric acid solution, and ultrasonically treated at 72°C for 48 minutes; then the mixture is transferred to a high-pressure reactor, 0.9 parts of silane coupling agent KH-550 are added, and hydrothermally reacted at 138°C for 96 minutes; after the reaction is completed, centrifugation is performed at 10400rpm, and the solid part is washed with 68.0 parts of deionized water until neutral; then the modified whiskers are dispersed in 100.0 parts of an aqueous solution containing 0.39 parts of ammonium polyacrylate, and ultrasonically treated for 32 minutes; the solid powder is filtered and collected, and finally dried at 92°C and 10⁻²Pa for 9.6 hours to obtain surface modified zirconia whiskers.

[0067] The surface-modified zirconium oxide whiskers of this embodiment have an average diameter of 1.4 μm and an average length of 13 μm.

[0068] The preparation method of the zirconium oxide whisker of the present embodiment is as follows: 2.0 parts of zirconium oxychloride octahydrate and 2.0 parts of mixed salt are weighed and placed in a mortar, wherein the mixed salt is sodium chloride and lithium chloride compounded in a mass ratio of 1:1.3, and the obtained solid mixture is fully ground for 22 minutes until it is uniform, and then the obtained precursor mixture is transferred to a corundum crucible with a cover, and placed in a high-temperature furnace, and heated to 960°C at a heating rate of 5.4°C / min at room temperature. After keeping warm for 312 minutes, the furnace power is then turned off, and the reaction system is allowed to cool naturally to room temperature with the furnace. The cooled solid product is washed 4.2 times with deionized water to remove residual molten salt, and dried at 72°C for 6.2 hours to finally obtain zirconium oxide whiskers.

[0069] The preparation method of the strontium titanate nanobelt of this embodiment is as follows: by weight, 27 parts of tetrabutyl titanate and 104 parts of ethylene glycol are mixed and ultrasonically treated for 13 minutes to obtain a suspension, then 19.2 parts of strontium chloride hexahydrate are added and ultrasonicated for 18 minutes, and then 56 parts of 4 mol / L KOH solution are added, followed by stirring at a stirring speed of 230 rpm for 13.6 minutes. After the stirring is completed, the mixed solution is transferred to a stainless steel autoclave lined with polytetrafluoroethylene, sealed and placed in a constant temperature oven at 184°C for a hydrothermal reaction for 21.6 h. After the reaction is completed, the heating source is turned off and the reactor is allowed to cool naturally to room temperature. The cooled reaction product is centrifuged at 9200 rpm for 13 to separate the precipitate, the filtrate is discarded, and the obtained precipitate is washed alternately with deionized water and anhydrous ethanol 4.2 times. The washed precipitate is transferred to a vacuum drying oven and dried at 68°C for 13h to obtain an off-white powder. The dried powder is transferred to a muffle furnace and heated to 720°C at a heating rate of 4.8°C / min. After keeping warm for 96 minutes, it is cooled to room temperature to obtain strontium titanate nanobelts.

[0070] The average width of the strontium titanate nanobelts in this embodiment is 72 nm, and the average length is 3.4 μm.

[0071] The volume ratio of ethanol to water in the ethanol and water mixed solution of this embodiment is 1:3.2.

[0072] A method for preparing a high-performance single-layer ceramic capacitor material in this embodiment includes the following steps:

[0073] S1. Precursor solution: barium nitrate and tetraisopropyl titanate are dissolved in a mixed solution of ethanol and water according to the weight ratio, and then tetramethylammonium hydroxide is slowly added. The mixture is ultrasonically treated at 280 W and 36 kHz for 39 min in a 40°C water bath to obtain a precursor solution.

[0074] S2. Pre-dispersion of the reinforcing phase: Add surface-modified zirconia whiskers and strontium titanate nanobelts to the above precursor solution, and add ammonium polyacrylate. Then, place the mixed slurry in a planetary ball mill, use zirconia ball media, and ball mill at 260 rpm for 96 minutes. The viscosity of the slurry after ball milling is 340 mPa·s.

[0075] S3. Doping and tape casting: Lanthanum oxide, niobium oxide, manganese dioxide, barium titanate nanoparticles and nano-silicon dioxide were added to the above slurry in sequence, and ultrasonic-mechanical stirring was used for coordinated treatment. The ultrasonic power was 460 W, the stirring rate was 540 rpm, and the treatment time was 39 min. Subsequently, a tape casting machine was used to form a wet film on the polyimide base film, and the film was cured at 36 ° C and 30% RH for 372 min to obtain a dry film.

[0076] S4. Gradient sintering treatment: Place the cured dry membrane in an atmosphere sintering furnace, and heat it to 580℃ at a rate of 4.2℃ / min under an oxygen flow rate of 80mL / min for organic matter removal treatment. The treatment time is 39min. Then, continue to heat it to 1190℃ at a rate of 4.2℃ / min for sintering. After sintering, anneal it in an oxygen atmosphere at 880℃ for 96min, and finally cool it in the furnace.

[0077] Embodiment 4: A high-performance single-layer ceramic capacitor material comprises the following raw materials in parts by weight: 12.0 parts of surface modified zirconium oxide whiskers, 18.0 parts of strontium titanate nanobelts, 75.0 parts of barium titanate nanoparticles, 8.0 parts of barium nitrate, 6.0 parts of tetraisopropyl titanate, 4.0 parts of tetramethylammonium hydroxide, 0.8 parts of ammonium polyacrylate, 2.0 parts of lanthanum oxide, 1.2 parts of niobium oxide, 0.5 parts of manganese dioxide, 0.8 parts of nano-silicon dioxide, and 100.0 parts of a mixed solution of ethanol and water.

[0078] The surface-modified zirconium oxide whisker is obtained by surface-modifying the zirconium oxide whisker with a silane coupling agent KH-550; the single-layer ceramic dielectric capacitor material comprises a barium titanate / strontium titanate coherent interface.

[0079] The preparation method of the surface modified zirconia whisker of the present embodiment is as follows: characterized in that: by weight, 12.0 parts of zirconia whiskers are immersed in 50.0 parts of 5.0 mol / L sulfuric acid solution, and ultrasonically treated at 80°C for 60 minutes; then the mixture is transferred to a high-pressure reactor, 1.2 parts of silane coupling agent KH-550 are added, and hydrothermally reacted at 150°C for 120 minutes; after the reaction is completed, centrifugation is performed at 12000 rpm, and the solid part is washed with 80.0 parts of deionized water until neutral; then the modified whiskers are dispersed in 100.0 parts of an aqueous solution containing 0.6 parts of ammonium polyacrylate, and ultrasonically treated for 40 minutes; the solid powder is filtered and collected, and finally dried at 100°C and 10⁻³Pa for 12 hours to obtain surface modified zirconia whiskers.

[0080] The surface-modified zirconia whiskers of this embodiment have an average diameter of 2.0 μm and an average length of 20 μm.

[0081] The preparation method of the zirconium oxide whisker of the present embodiment is as follows: 2.2 parts of zirconium oxychloride octahydrate and 2.2 parts of mixed salt are weighed and placed in a mortar, wherein the mixed salt is sodium chloride and lithium chloride compounded in a mass ratio of 1:1.5, and the obtained solid mixture is fully ground for 30 minutes until it is uniform, and then the obtained precursor mixture is transferred to a corundum crucible with a cover, and placed in a high-temperature furnace, and heated to 1000°C at a heating rate of 7°C / min at room temperature. After keeping the temperature for 360 minutes, the furnace power is then turned off, and the reaction system is allowed to cool naturally to room temperature with the furnace. The cooled solid product is washed with deionized water 5 times to remove residual molten salt, and dried at 80°C for 7 hours to finally obtain zirconium oxide whiskers.

[0082] The preparation method of strontium titanate nanobelts in this embodiment is as follows: by weight, 34 parts of tetrabutyl titanate and 120 parts of ethylene glycol are mixed and ultrasonically treated for 15 minutes to obtain a suspension, then 24.0 parts of strontium chloride hexahydrate are added and ultrasonicated for 20 minutes, and then 60 parts of 4 mol / L KOH solution are added, followed by stirring at a stirring speed of 250 rpm for 16 minutes. After the stirring is completed, the mixed solution is transferred to a stainless steel autoclave lined with polytetrafluoroethylene, sealed and placed in a constant temperature oven at 200°C for hydrothermal reaction for 24 hours. After the reaction is completed, the heating source is turned off and the reactor is allowed to cool naturally to room temperature. The cooled reaction product is centrifuged at a centrifugal rate of 10,000 rpm for 15 to separate the precipitate, the filtrate is discarded, and the obtained precipitate is washed alternately with deionized water and anhydrous ethanol for 5 times. The washed precipitate is transferred to a vacuum drying oven and dried at 80°C for 15h to obtain an off-white powder. The dried powder is transferred to a muffle furnace and heated to 800°C at a heating rate of 6°C / min. After keeping warm for 120 minutes, it is cooled to room temperature to obtain strontium titanate nanobelts.

[0083] The average width of the strontium titanate nanobelts in this embodiment is 100 nm, and the average length is 5 μm.

[0084] The volume ratio of ethanol to water in the ethanol and water mixed solution of this embodiment is 1:4.0.

[0085] A method for preparing a high-performance single-layer ceramic capacitor material in this embodiment includes the following steps:

[0086] S1. Precursor solution: barium nitrate and tetraisopropyl titanate were dissolved in a mixed solution of ethanol and water according to the weight ratio, and then tetramethylammonium hydroxide was slowly added. The mixture was ultrasonically treated at 300 W and 40 kHz for 45 min in a 40°C water bath to obtain a precursor solution.

[0087] S2. Pre-dispersion of the reinforcing phase: Add surface-modified zirconia whiskers and strontium titanate nanobelts to the above precursor solution, and add ammonium polyacrylate. Then, place the mixed slurry in a planetary ball mill, use zirconia ball media, and ball mill at 300 rpm for 120 minutes. The viscosity of the slurry after ball milling is 400 mPa·s.

[0088] S3. Doping and tape casting: Lanthanum oxide, niobium oxide, manganese dioxide, barium titanate nanoparticles and nano-silicon dioxide were added to the above slurry in turn, and ultrasonic-mechanical stirring was used for coordinated treatment. The ultrasonic power was 500 W, the stirring rate was 600 rpm, and the treatment time was 45 min. Subsequently, a tape casting machine was used to form a wet film on the polyimide base film, and the film was cured at 40°C and 30% RH for 420 min to obtain a dry film.

[0089] S4. Gradient sintering treatment: Place the cured dry membrane in an atmosphere sintering furnace, and at an oxygen flow rate of 100 mL / min, heat it to 600°C at a rate of 5°C / min for organic matter removal treatment. The treatment time is 45 minutes. Subsequently, heat it to 1250°C at a rate of 5°C / min for sintering. After sintering, anneal it in an oxygen atmosphere at 900°C for 120 minutes, and finally cool it in the furnace.

[0090] Comparative Example 1

[0091] The method is substantially the same as Example 1, except that the surface of the zirconium oxide whiskers is not modified.

[0092] Comparative Example 2

[0093] It is basically the same as Example 1, except that strontium titanate nanobelts are not added.

[0094] Comparative Example 3

[0095] The method is substantially the same as Example 1, except that tetramethylammonium hydroxide is not added.

[0096] Comparative Example 4

[0097] It is basically the same as Example 1, except that ammonium polyacrylate is not added.

[0098] Comparative Example 5

[0099] The method is basically the same as Example 1, except that manganese dioxide is not added.

[0100] Comparative Example 6

[0101] The method is basically the same as Example 1, except that no nano silicon dioxide is added.

[0102] Comparative Example 7

[0103] The method is basically the same as Example 1, except that the volume ratio of ethanol to water is adjusted to 1:1.

[0104] Comparative Example 8

[0105] It is basically the same as Example 1, except that the annealing temperature is reduced to 700°C.

[0106] Comparative Example 9

[0107] The method is basically the same as Example 1, except that the 3.0 mol / L sulfuric acid solution is not used to pretreat the zirconium oxide whiskers, and the surface modification is directly performed.

[0108] Comparative Example 10

[0109] The method is basically the same as Example 1, except that the hydrothermal reaction temperature of the surface-modified zirconium oxide whiskers is reduced from 120°C to 90°C.

[0110] Comparative Example 11

[0111] The method is basically the same as Example 1, except that the amount of silane coupling agent KH-550 is reduced from 0.4 parts to 0.1 parts.

[0112] Comparative Example 12

[0113] The method is basically the same as Example 1, except that the hydrothermal reaction temperature of the strontium titanate nanobelts is reduced from 160°C to 120°C.

[0114] Performance Test:

[0115] Dielectric constant and dielectric loss test: The dielectric constant (εr) and dielectric loss (tanδ) of the material are measured in the frequency range of 1kHz~1MHz using the precision LCR tester Agilent4284A. The test sample is prepared as a disc electrode structure with a diameter of 10mm and a thickness of 1mm, and gold electrodes are sputtered on the sample surface to ensure good contact.

[0116] Insulation resistance and breakdown field strength test: The volume resistivity of the material is tested using a high resistance meter Keithley 6517B, and a DC high voltage power supply (Spellman SL150) is used to apply an electric field, measure the breakdown voltage, and calculate the breakdown field strength (kV / mm).

[0117] Mechanical strength test: The flexural strength was measured by a three-point bending test Instron 5967, and the fracture toughness KIC was calculated by a single-edge notch bending method.

[0118] The properties of the single-layer ceramic capacitor materials of Examples 1 to 4 and Comparative Examples 1 to 12 are summarized in Table 1.

[0119] Table 1 Performance of single-layer ceramic capacitor materials of Examples 1 to 4 and Comparative Examples 1 to 12

[0120]

[0121] The lack of SrO2 nanoribbons or the reduction of annealing temperature will lead to a significant decrease in the dielectric constant, indicating that these factors play a key role in improving the polarization ability of the material. At the same time, the unmodified zirconia whiskers or the reduction of annealing temperature will lead to a significant increase in dielectric loss, indicating that the microstructure and interface uniformity of the material are crucial to reducing dielectric loss. In addition, factors affecting the uniformity of the material, such as imperfect surface treatment of zirconia whiskers or changes in hydrothermal reaction conditions, will cause a decrease in the breakdown field strength, indicating that the density and defect control of the material have a direct impact on the dielectric strength. In terms of electrical properties, changes in sintering quality or interface problems will cause a significant decrease in volume resistivity, indicating that optimizing the sintering process and interface engineering are crucial to improving the insulation properties of the material. In terms of mechanical properties, the unmodified zirconia whiskers or the reduction of annealing temperature will lead to a significant decrease in flexural strength, indicating that the surface treatment of zirconia whiskers helps to enhance the matrix bonding and improve the toughness of the material. In addition, the lack of SrO2 nanoribbons or the reduction of hydrothermal reaction temperature will also affect the flexural strength and fracture toughness, indicating that the reasonable introduction of SrO2 nanostructures can help improve the mechanical properties of the material. In general, the modification of zirconium oxide whiskers, the introduction of strontium titanate nanobelts, the appropriate annealing temperature and the optimized hydrothermal reaction conditions all play a vital role in improving the dielectric properties, insulation and mechanical strength of the material. However, some factors, such as the adjustment of the ratio of manganese dioxide, nanosilica or solvent, have relatively little effect on the overall performance, indicating that the optimization of these minor factors is more for improving the process adaptability and stability of the material.

[0122] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that all equivalent structural changes made under the concept of the present invention and using the contents of the present invention specification and drawings should be covered within the scope of protection of the claims of the present invention.

Claims

1. A high performance single-layer ceramic capacitor material, characterized in that: The invention comprises the following raw materials in parts by weight: 8.0-12.0 parts of surface modified zirconium oxide whiskers, 10.0-18.0 parts of strontium titanate nanobelts, 60.0-75.0 parts of barium titanate nanoparticles, 5.0-8.0 parts of barium nitrate, 4.0-6.0 parts of tetraisopropyl titanate, 2.0-4.0 parts of tetramethylammonium hydroxide, 0.3-0.8 parts of ammonium polyacrylate, 1.0-2.0 parts of lanthanum oxide, 0.5-1.2 parts of niobium oxide, 0.1-0.5 parts of manganese dioxide, 0.3-0.8 parts of nano silicon dioxide, and 100.0 parts of a mixed solution of ethanol and water; The surface-modified zirconium oxide whiskers are obtained by surface-modifying zirconium oxide whiskers with a silane coupling agent KH-550; The single-layer ceramic capacitor material comprises a barium titanate / strontium titanate coherent interface.

2. A high performance single-layer ceramic capacitor material as claimed in claim 1, characterized in that: The preparation method of the surface modified zirconium oxide whisker is characterized in that: by weight, 8.0-12.0 parts of zirconium oxide whisker are immersed in 30.0-50.0 parts of 3.0-5.0 mol / L sulfuric acid solution, and ultrasonically treated at 60-80° C. for 30-60 min; then the mixture is transferred to a high-pressure reactor, 0.4-1.2 parts of silane coupling agent KH-550 are added, and hydrothermally reacted at 120-150° C. for 60-120 min. in; after the reaction is completed, centrifuge at 8000~12000rpm, and wash the solid part with 50.0~80.0 parts of deionized water until neutral; then disperse the modified whiskers in 100.0 parts of an aqueous solution containing 0.18~0.6 parts of ammonium polyacrylate, and ultrasonically treat for 20~40min; filter and collect the solid powder, and finally dry it at 80~100℃ and 10⁻²~10⁻³Pa for 6~12 hours to obtain surface-modified zirconia whiskers.

3. A high performance single-layer ceramic capacitor material as claimed in claim 1 or 2, characterized in that: The surface modified zirconium oxide whiskers have an average diameter of 0.5-2.0 μm and an average length of 5-20 μm.

4. A high performance single-layer ceramic capacitor material as claimed in claim 1, characterized in that: The preparation method of the zirconium oxide whisker is as follows: 1.8-2.2 parts of zirconium oxychloride octahydrate and 1.8-2.2 parts of mixed salt are weighed and placed in a mortar, wherein the mixed salt is sodium chloride and lithium chloride compounded in a mass ratio of 1:(1-1.5), the obtained solid mixture is fully ground for 10-30 minutes until it is uniform, and then the obtained precursor mixture is transferred to a corundum crucible with a cover, and placed in a high-temperature furnace, and heated to 900-1000°C at a heating rate of 3-7°C / min at room temperature, and after keeping the temperature for 240-360 minutes, the furnace power is then turned off, and the reaction system is naturally cooled to room temperature with the furnace, and the solid product after cooling is washed with deionized water for 3-5 times to remove residual molten salt, and is dried at 60-80°C for 5-7 hours, so as to finally obtain the zirconium oxide whisker.

5. A high performance single-layer ceramic capacitor material as claimed in claim 1, characterized in that: The preparation method of the strontium titanate nanobelt is as follows: by weight, 17-34 parts of tetrabutyl titanate and 80-120 parts of ethylene glycol are mixed and ultrasonically treated for 10-15 minutes to obtain a suspension, then 12.0-24 parts of strontium chloride hexahydrate are added and ultrasonically treated for 15-20 minutes, and then 50-60 parts of 4 mol / L KOH solution are added, and then stirred at a stirring speed of 200-250 rpm for 10-16 minutes. After the stirring is completed, the mixed solution is transferred to a stainless steel autoclave lined with polytetrafluoroethylene, sealed and placed in a constant temperature oven at 160-200°C, and hydrothermally reacted for 18- 24h, after the reaction is completed, turn off the heating source and allow the reactor to cool naturally to room temperature. The cooled reaction product is separated by centrifugation at a centrifugal rate of 8000~10000rpm for 10~15 to separate the precipitate, the filtrate is discarded, and the obtained precipitate is washed alternately with deionized water and anhydrous ethanol for 3~5 times in turn. The washed precipitate is transferred to a vacuum drying oven and dried at 50~80℃ for 10~15h to obtain an off-white powder. The dried powder is transferred to a muffle furnace and heated to 600~800℃ at a heating rate of 3~6℃ / min. After keeping warm for 60~120min, it is cooled to room temperature to obtain strontium titanate nanobelts.

6. A high performance single-layer ceramic capacitor material as claimed in claim 1 or 5, characterized in that: The average width of the strontium titanate nanobelt is 30-100 nm, and the average length is 1-5 μm.

7. A high performance single-layer ceramic capacitor material as claimed in claim 1, characterized in that: The volume ratio of ethanol to water in the ethanol and water mixed solution is 1: (2.0-4.0).

8. The method for preparing a high-performance single-layer ceramic capacitor material according to claim 1, characterized in that: The following steps are involved: S1. Precursor solution: barium nitrate and tetraisopropyl titanate are dissolved in a mixed solution of ethanol and water according to a weight ratio, and then tetramethylammonium hydroxide is slowly added, and ultrasonic treatment is performed at 250-300W and 30-40kHz for 30-45min in a 40°C water bath to obtain a precursor solution; S2. Pre-dispersion of the reinforcing phase: Add the surface-modified zirconium oxide whiskers and strontium titanate nanobelts to the above-mentioned precursor solution, and add ammonium polyacrylate. Then, place the mixed slurry in a planetary ball mill, use zirconium oxide ball media, and ball mill at a speed of 200-300 rpm for 60-120 min. The viscosity of the slurry after ball milling is 250-400 mPa·s. S3. Doping and tape casting: Lanthanum oxide, niobium oxide and manganese dioxide, barium titanate nanoparticles and nano-silicon dioxide were added to the above slurry in sequence, and ultrasonic-mechanical stirring was used for synergistic treatment. The ultrasonic power was 400~500W, the stirring rate was 450~600rpm, and the treatment time was 30~45min. Then, a wet film was formed on the polyimide base film using a tape casting machine, and cured at 30~40°C and 30%RH for 300~420min to obtain a dry film. S4. Gradient sintering treatment: Place the cured dry membrane in an atmosphere sintering furnace, and at an oxygen flow rate of 50~100mL / min, heat it to 550~600℃ at a rate of 3~5℃ / min for organic matter removal treatment. The treatment time is 30~45min. Then, continue to heat it to 1100~1250℃ at a rate of 3~5℃ / min for sintering. After sintering, anneal it in an oxygen atmosphere at 850~900℃ for 60~120min, and finally cool it in the furnace.

Citation Information

Patent Citations

  • High-specific capacitance thin-film capacitor graphene barium titanate polyimide composite film material and preparation method thereof

    CN106633142A

  • Medium-high voltage ceramic dielectric capacitor material with bias characteristic for medium temperature sintering

    CN106187166A

  • Dielectric porcelain composition

    JP2005170732A